Determination of affinity and efficacy of acetylcholinesterase inhibitors using isothermal titration calorimetry - Draczkowski, Piotr; Tomaszuk, Anna; Halczuk, Pawel; Strzemski, Maciej; Matosiuk, Dariusz; Jozwiak, Krzysztof (Biochimica et biophysica acta, 2016)
Acetylcholinesterase (AChE), an enzyme rapidly terminating nerve signals at synapses of cholinergic neurons is an important drug target in treatment of Alzheimer's disease and related memory loss conditions. Here we present comprehensive use of isothermal titration calorimetry (ITC) for investigation of AChE kinetics and AChE-inhibitor interactions. Acetylcholinesterase (AChE, EC 3.1.1.7) from Electrophorus electricus was assayed for interactions with five well known AChE inhibitors, galanthamine, tacrine, donepezil, edrophonium and ambenonium. In ITC experiments the inhibitors were injected to the enzyme solution solely (for thermodynamic characterization of binding) or in presence of the substrate, acetylcholine (for determination of inhibitors potency). Detailed description of various experimental protocols is presented, allowing evaluation of inhibitors potency (in terms of IC50 and Ki) and thermodynamic parameters of the binding. The potency of tested inhibitors was in nano to micromolar range which corresponded to activities determined in conventional method. Binding of all inhibitors showed to be enthalpy driven and obtained Ka values demonstrated good correlation with the data from standard Ellman's assay. Obtained results confirmed the usability of the ITC technique for comprehensive characterization of AChE-inhibitor interactions and AChE kinetics. The method reduced the complexity of reaction mixture and interference problems with the advantage of using natural substrates. The work reports complete thermodynamic characteristics of the AChE — inhibitor complexes. Due to the universal character of ITC measurements, described protocols can be easily adapted to other enzymatic systems. This article is part of a Special Issue entitled Microcalorimetry in the BioSciences — Principles and Applications, edited by Fadi Bou-Abdallah. [Display omitted] •Isothermal titration calorimetry is applied to study acetylcholinesterase (AChE).•ITC is a label free method to measure the AChE kinetics.•Further, it is employed to assess activity and affinity of AChE inhibitors.•Finally, it allows for thermodynamic characterization of AChE-inhibitor interaction.